Is there room for AI authorship – navigating the legal status and copyright protection in the European Union - Salmi, Martta (My University, 2025)
This legal dogmatic thesis examined how the concepts of artificial intelligence (AI) and authorship and copyright requirements have been interpreted in literature such as Tekijänoikeus (2024) by Harenko, Kivistö, Niiranen, and Tarkela, Originality in EU Copyright (2013) by Rosati and scholarly articles. Other main sources included international conventions, European Union (EU) legislation, and judgements both in the EU and the United States (U.S.) and other relevant jurisdictions. Based on the analysis, the EU copyright system remains strongly based on the principle that authorship is linked to the author’s free and creative choices, reflecting their personality and their own intellectual contribution and effort. The U.S. system similarly requires human originality and works produced solely by AI have fallen outside the scope of protection for the time being. Similar approaches have been adapted in other jurisdictions, at least by granting rights to a natural person utilising AI as a tool. While discourse continues regarding AI’s increasing role in creative industries, the prevailing doctrinal consensus in the jurisdictions overviewed still rejects the notion of AI as an author and purely AI-generated works remain outside the protective scope. Although the member states of the EU seem to currently favour sector-specific reforms, it is argued that limited forms of protection could offer a pragmatic solution for works involving some degree of human creative input, without undermining the core principles of copyright. For example, contractual solutions remain a practical arrangement for commercial benefits. Ultimately, the essence of copyright lies in its human-centric foundation, justifications and incentives. Creativity is viewed as an expression of human personality, choices, and intellect. Recognising AI as an author in the existing situation would alter this understanding. While technology continues to challenge existing legal frameworks, the connection between authorship and human creativity remains central to the coherence and legitimacy of EU copyright law.
Keywords: copyright, artificial intelligence, EU law